Lutetian calcareous nannofossil events in the Agost section (Spain): implications toward a revision of the Middle Eocene biomagnetostratigraphy. (18th June 2013) - Tori, Flavia; Monechi, Simonetta
<x xml:space="preserve">Abstract</x> This paper presents a detailed calcareous nannofossil biostratigraphy of the entire Lutetian of the Agost section (Betic Cordillera, SE Spain). This investigation integrates and improves on previous study performed through the Ypresian/Lutetian boundary by the authors on this succession. The new revision of the integrated bio‐magnetobiochronology of the Early/Middle Eocene interval revealed highly diversified calcareous nannofossil assemblages, characterizing more than 8 Myr of climatic variability. The studied interval spans from Zone CP11 to Subzone CP14a and from the upper part of Zone NP13 to the base of Zone NP16 of calcareous nannofossil standard zonations. The revision of the calcareous nannofossil content enabled the identification of numerous secondary events which greatly improved the stratigraphic resolution of this time interval. An important re‐organization of the nannoflora was observed during the Y/L transition, when Reticulofenestra and Dictyococcites (Noelaerhabdaceae) became the most important genera in terms of abundance and dispersal, dominating the Middle Eocene nannofossil assemblages and replacing Toweius and Discoaster taxa characteristic of the lower Eocene. Pentaliths and Blackites experience a great expansion and diversification, whereas Discoaster and Chiasmolithus which are well diversified but never abundant during the Lutetian show a slow turnover. A reassessment of the major bio‐events observed in the Noelaerhabdaceae family as well as revision and correlation of these events with the classical Italian sections (Contessa and Bottaccione) are presented. The new results show that biostratigraphic problems related to the Middle Eocene chronology are not limited to the correlation between calcareous nannofossils and planktonic foraminiferans at the Y/L transition but extend to calcareous nannofossil events commonly used for correlating the Bartonian.